Diverse MicroRNAs‐mRNA networks regulate the priming phase of mouse liver regeneration and of direct hyperplasia. Issue 4 (17th February 2022) - Pal, Rajesh; Kowalik, Marta Anna; Serra, Marina; Migliore, Cristina; Giordano, Silvia; Columbano, Amedeo; Perra, Andrea
Abstract: Objectives: Adult hepatocytes are quiescent cells that can be induced to proliferate in response to a reduction in liver mass (liver regeneration) or by agents endowed with mitogenic potency (primary hyperplasia). The latter condition is characterized by a more rapid entry of hepatocytes into the cell cycle, but the mechanisms responsible for the accelerated entry into the S phase are unknown. Materials and methods: Next generation sequencing and Illumina microarray were used to profile microRNA and mRNA expression in CD‐1 mice livers 1, 3 and 6 h after 2/3 partial hepatectomy (PH) or a single dose of TCPOBOP, a ligand of the constitutive androstane receptor (CAR). Ingenuity pathway and DAVID analyses were performed to identify deregulated pathways. MultiMiR analysis was used to construct microRNA‐mRNA networks. Results: Following PH or TCPOBOP we identified 810 and 527 genes, and 102 and 10 miRNAs, respectively, differentially expressed. Only 20 genes and 8 microRNAs were shared by the two conditions. Many miRNAs targeting negative regulators of cell cycle were downregulated early after PH, concomitantly with increased expression of their target genes. On the contrary, negative regulators were not modified after TCPOBOP, but Ccnd1 targeting miRNAs, such as miR‐106b‐5p, were downregulated. Conclusions: While miRNAs targeting negative regulators of the cell cycle are downregulated after PH, TCPOBOP caused downregulation of miRNAs targeting genes required for cell cycle entry. The enhanced Ccnd1 expression may explain the more rapid entry into the S phase of mouse hepatocytes following TCPOBOP. Abstract : A balance of pro‐ and anti‐proliferative signals is regulated by miRs in the priming phase of hepatocytes following pH‐induced liver regeneration, while miR deregulation leads only to pro‐proliferative signals in primary hyperplasia. This justifies the more rapid entry of hepatocytes into the cell cycle after TCPOBOP treatment.